PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS AUGMENTED REALITY PADA PEMBELAJARAN IPAS MATERI HARMONI DALAM EKOSISTEM KELAS V SEKOLAH DASAR : Penelitian R&D - Natasya Zahrah; Putri Khoirunnisa; Taofik; Anggi Citra Apriliana (STKIP Subang, 2024)
Based on observation and needs analysis, innovative technology-based learning media is needed in class V of SDN Karet 01 in the science and science subject on harmony in ecosystems. This research aims to produce a product in the form of augmented reality learning media for science and science learning and to determine the validation results and feasibility of augmented reality learning media in class V at SDN Karet 01. The subjects in this research are class V students at SDN Karet 01. The development model used in the research this is the ADDIE (analyze, design, development, implementation and evaluation) development model. Data collection techniques were carried out by observation, interviews and questionnaires. The data analysis model used is the Miles and Huberman analysis model. The results of trials developing augmented reality learning media with media experts, material experts and language experts obtained an average score of 88% in the